Human Rights Practice: A Means to Environmental Ends? - Kate Donald (Oñati Socio-Legal Series)
Can human rights practice in its current dominant forms tackle the challenge of climate change and global environmental degradation? This article argues that although there is now increased recognition of the links between human rights and the environment, and while human rights tools and principles can contribute in some concrete ways in moving forward the environmental agenda, their potential for doing is so far largely unrealised. The article analyses three different approaches used by advocates and activists in this field, before discussing potential alternatives and examples of radical or hybrid approaches, with a view to articulating a strategy for activism and praxis that can capture the real and lived inter-connectedness of human rights enjoyment and environmental factors more meaningfully.